Predictors for long-term disability in women with persistent postpartum pelvic girdle pain - Sjödahl, Jenny (Springer Berlin Heidelberg, 2013)
PURPOSE: The majority of prognostic studies on postpartum lumbopelvic pain have investigated factors during pregnancy. Since the majority of women recover within the first few months of delivery, it is unknown if the same predictors are valid for long-term consequences. It is also important to investigate predictors within subgroups of patients with pregnancy-related lumbopelvic pain due to their different clinical courses. The aim of this study was to identify predictors for disability 15 months postpartum in women with persistent postpartum pelvic girdle pain (PGP). METHODS: Data were obtained by clinical tests and questionnaires 3 months postpartum. The outcome 15 months postpartum was disability measured with the Oswestry Disability Index. RESULTS: A multiple linear regression analysis identified two significant two-way interaction effects that were predictive of disability 15 months postpartum: (a) age + trunk flexor endurance, and (b) disability + hip extensor strength. CONCLUSIONS: Age, muscle function and disability seem to influence the long-term outcome on disability in women with persistent postpartum PGP. It may be important to consider the possibility of different variables impact on each other when predicting long-term disability. In addition, further studies are needed to investigate the impact of interaction effects on long-term consequences in women with persistent postpartum PGP.